The presindent´s murderer - Bassett, Jennifer (Oxford bookworms 1)
The president is dead! A man is running in the night. He is afraid and needs to rest. But there are people behind him- people wiht lights, and dogs, and guns. A man is standing in front of desk. His boss is very angry, and the man is tired and needs to sleep. But first he must find the other man, and bring him back - dead or alive. Two men: the hunter and the hunted. Which will win and which will lose? Long live the president!